Analysis of atypical glandular cells in ThinPrep Pap smear and follow-up histopathology. - Wang, Tengfei; Hua, Yinan; Liu, Lina; Leng, Bing (Baylor University Medical Center Proceedings, 2024)
Diagnosing atypical glandular cells (AGC) is a significant challenge in cytomorphology. A retrospective study was undertaken to assess the prevalence of AGC and the subsequent histological outcomes over 5 years at a single institution. A total of 159,649 ThinPrep Pap tests, including 395 cases of AGC, were retrieved, of which 330 AGC cases had follow-up histopathology. Among these 330 cases, 43.9% were classified as AGC not otherwise specified, followed by AGC-endocervical cells at 33.3%. The most frequently observed histological findings at follow-up included CIN1 and benign mucosa with reactive changes, followed by high-grade squamous intraepithelial lesion and cervical squamous cell carcinoma. The overall 5-year insignificant AGC rate was 0.12%, and the overall 5-year significant AGC rate was 0.08%. Notably, 36.7% of AGC cases tested positive for high-risk human papillomavirus. Interestingly, the level of experience did not significantly impact the rates for significant or insignificant AGC diagnosis. However, senior cytopathologists had a higher AGC report rate compared to their junior peers. The AGC diagnostic rate at our institution falls within the range given by the College of American Pathologists. A significant number of cases had follow-up histologic results available, and the overall 5-year insignificant AGC rate was 0.12%.